The obesity paradox effect of triglyceride-glucose-body mass index (TyG-BMI) on all-cause mortality in patients with malignant tumors: a machine learning-driven cohort study - Wang, Mingxing; Li, Yahao; Chen, Jian; Dong, Wanhui; Wang, Yuru; Bo, Siyi; Wu, Pantong; Wang, Zhiying; Zhong, Zhixian; Zhong, Yi (Translational Cancer Research, 2026)
The prognostic significance of the triglyceride-glucose (TyG) index and its adiposity-related derivatives—incorporating body mass index (TyG-BMI), waist circumference (TyG-WC), and waist-to-height ratio (TyG-WHtR)—remains underexplored in patients with malignancies. This study aimed to systematically evaluate their predictive value for all-cause, cancer-specific, and cardiovascular disease (CVD) mortality utilizing traditional survey-weighted Cox regression and advanced machine learning (ML) algorithms.